Staggered SAR: High-Resolution Wide-Swath Imaging by Continuous PRI Variation - Villano, Michelangelo; Krieger, Gerhard; Moreira, Alberto (IEEE Transactions on Geoscience and Remote Sensing, 2014)
Synthetic aperture radar (SAR) is a remote sensing technique, capable of providing high-resolution images independent of weather conditions and sunlight illumination. This makes SAR very attractive for the systematic observation of dynamic processes on the Earth′s surface. However, conventional SAR systems are limited, in that a wide swath can only be achieved at the expense of a degraded azimuth resolution. This limitation can be overcome by using systems with multiple receive apertures, displaced in along-track, but a very long antenna is required to map a wide swath. If a relatively short antenna with a single aperture in along-track is available, it is still possible to map a wide area: Multiple swaths can be, in fact, simultaneously imaged using digital beamforming in elevation, but ``blind ranges″ are present between adjacent swaths. This paper considers an innovative concept, Staggered SAR, where the pulse repetition interval (PRI) is continuously varied. This concept allows the imaging of a wide continuous swath without the need for a long antenna with multiple apertures. The choice of the sequence of PRIs and the pre-processing of the raw data are discussed in detail, showing how Staggered SAR is even less affected by ambiguities of point-like or extended targets with respect to a system with constant PRI, which simultaneously maps multiple swaths. Some system design examples are finally presented and compared.
DLR Import::2019-04-02
Keywords: Interpolation; microwave remote sensing; radar data processing; synthetic aperture radar; System analysis and design